High production of fumaric acid from xylose by newly selected strain Rhizopus arrhizus RH 7-13-9#. (June 2015) - Liu, Huan; Wang, Weinan; Deng, Li; Wang, Fang; Tan, Tianwei
Highlights: A strain using a high concentration of xylose was selected by an efficient method. A high fumaric acid production and volumetric productivity was obtained. The conversion of xylose reached 73%, close to the theoretical value (77%). Abstract: Fumaric acid, as an important material for polymerization, is highly expected to be produced by fermentation of lignocellulosic biomass which is composed of cellulose, hemicellulose and lignin. Xylose as the main component of hemicellulose cannot be efficiently utilized by most of the common fermentation. In this study, a new strain Rhizopus arrhizus RH 7-13-9# was selected from the R. arrhizus RH 7-13 through a novel convenient and efficient selection method. Efficient production of fumaric acid (45.31 g/L) from xylose was achieved by the new strain, and the volumetric productivity was still 0.472 g/L h. Moreover, the conversion of xylose reached 73% which is close to the theoretic yield (77%). The production of fumaric acid was increased approximate by 172%, compared with the initial strain counterpart. These results indicated that xylose, as the main component of hemicellulose, has a promising application for the production of fumaric acid on an industrial-scale.